THE ROLE OF RESILIENCE IN OVERCOMING MENTAL HEALTH PROBLEMS AMONG DRUG ADDICTS AT THE NATIONAL NARCOTICS AGENCY OF NORTH SUMATRA PROVINCE - Petra Johanna; Gio Vanny Valentina Zai; Sinta Surabina Br Tarigan; Agnes Mehuli Tarigan; Winida Marpaung (SOSIOEDUKASI, 2026)
Drug abuse has serious impacts on both physical and mental health, particularly among individuals in early adulthood. The rehabilitation process is often accompanied by psychological pressure arising from experiences of detention, family conflicts, and social stigma. This study aims to examine the role of resilience in addressing mental health among drug addicts at the National Narcotics Agency of North Sumatra Province. This research employed a qualitative method using observation and in-depth interviews. The subjects consisted of three male early-adult drug users selected through purposive sampling, with criteria of individuals aged 18–40 years who were undergoing outpatient rehabilitation at the National Narcotics Agency of North Sumatra Province. The resilience theory used in this study refers to Reivich and Shatté (as cited in Hardiana & Dewi, 2023), which explains that resilience is the ability of individuals to endure, recover, and adapt positively when facing pressure or difficult life experiences, enabling them to function effectively. This ability is reflected through seven factors: emotional regulation, impulse control, causal analysis, self-efficacy, optimism, empathy, and reaching out. The results indicate that drug use is influenced by peer environment, family pressure, and the need for social acceptance. During detention, participants experienced psychological distress such as stress, anxiety, feelings of pressure, and loneliness. Among the seven resilience factors, family support, humane rehabilitation conditions, and optimism were the most significant in fostering resilience, as participants expressed a strong desire to change, avoid disappointing their families, and improve their future.